Penguatan Pendidikan Karakter Siswa Melalui Manajemen Bimbingan dan Konseling Islam - Isnaini, Rohmatun Lukluk (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2016)
The importance of character education is a wisdom of value diversity and social live culture. To achive the goal, the education system in school has developed three sub systems,namely, administration, instruction, and pupil/ student personal service. Guidance andcounseling program is from pupil/ student personal service. Strengthening charactereducation can be realized through the management of Islamic guidance and counseling.According to management concept, implementation of guidance and counselingmanagement isone of the manivestation of systematic program on how to plan guidanceand counseling activity, how to lead human resource in the organization in order toachieve the goal, how to control the activity of guidance and counseling, andhow toevaluate it. Therefore, the management of Islamic guidance and counselingcan achievethe education goal exspecially in strengthening education character.